Optimization of the laser-assisted tape winding process using an inverse kinematic-optical-thermal model - S. M. Amin Hosseini (Taylor & Francis Group, 2020)
A new inverse kinematic-optical-thermal (IKOT) model is introduced to control the process temperature in laser assisted tape winding and placement processes. The optimum time-dependent laser power distribution is obtained by employing a grid of independent laser cells while keeping the temperature of substrate and tape at the target temperature. Multi-layer cylindrical hoop winding with laser grids of 1 × 1, 28 × 1, and 28 × 11 and helical winding of a pressure vessel with laser grids of 22 × 1 and 22 × 11 are considered. It is found that the optimized laser power distribution pattern remains the same during the consecutive hoop winding process while the total power reduces to compensate the heat accumulation. A more non-uniform laser power distribution is obtained for the helical winding because the substrate curvature changes drastically at the dome section of the pressure vessel. The change in the optimum total laser power is found to be almost constant for the helical winding case. Finally, the IKOT model is evaluated by analyzing the effect of the computational parameters on the optimized process temperature.